Dermatitis Dishidrotik - Mohamad Mimbar Topik; Dara Gebrina Rizki (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Dyshidrotic dermatitis is a form of hand and foot dermatitis characterized by fluid accumulation in the form of vesicles or bullae. Dyshidrotic dermatitis is the most common form of skin disease, accounting for up to 80% of people of all ages and genders. The etiology of dyshidrotic dermatitis is idiopathic, but some sources link the etiology with a history of atopy. There are also sources that state that the etiology of dyshidrotic dermatitis is a combination of various factors, such as environmental and genetic factors. Pathogenesis of dyshidrotic dermatitis, states that dyshidrotic dermatitis vesicles are caused by sweat gland dysfunction. However, it turns out that the histological examination of the sweat gland ducts is not abnormal. However, hyperhidrosis (excessive sweating) is found in almost a third of dyshidrosis dermatitis sufferers and can also be associated with atopic dermatitis, contact dermatitis, or reactions to systemic drugs. (anti-retrovirals, intravenous immunoglobulin, mycophenolate-mofetil immunosuppressant). Treatment can be in the form of corticosteroids and emollients are the main choice in management of dyshidrotic dermatitis. Other therapies such as retinoids and Immumomodulators may also be considered according to clinical conditions patient dyshidrotic dermatitis, is a chronic and recurrent disease, so the patient must be controlled periodically and receive education to avoid precipitating facto.